Reviewing the Federal Employment Equity Act - , (Canadian Woman Studies/les cahiers de la femme, 1992)
- Canadian Labour Congress- Canadian Federation of Business and Professional Women's Clubs- Saskatchewan Wheat Pool/Grain Services Union- Communications and Electrical Workers of Canada- Manitoba Telephone System